Moisture Desorption and Adsorption Chareteristics of Gum Arabic from Acacia senegal and A. seyal (University of Khartoum Journal of Agricultural Sciences, 2023)
The objective of this paper was to study the moisture isothermscharacteristics of gum Arabic produced by Acacia senegal and A. seyal.The equilibrium moisture content of the gum was determined by thestandard static gravimetric methods using various saturated salts solutionsin closed desiccators to provide a range of RH of 0 to 96%. Gum sampleswere placed in these desiccators, and kept inside the oven at specifiedtemperature (30, 40, 50 and 60°C) until equilibrium moisture content wasobtained. Desorption and adsorption isotherms of gum Arabic exhibitedsigmoid curves and indicated clear hysteresis effect. The statisticalanalysis indicated that the relationship between equilibrium moisturecontent and RH could be well explained by third-order polynomialfunctions. Equilibrium moisture content increased with increase in RHbut decreased with increase in temperature
Keywords: Sorption isotherms; equilibrium moisture content; gum Arabic; polynomial functions; drying